2021
DOI: 10.2147/ijgm.s343216
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Related Gene-Based Signature Can Evaluate the Tumor Immune Microenvironment and Predict the Prognosis of Colon Adenocarcinoma Patients

Abstract: Background Colon adenocarcinoma (COAD) is a common gastrointestinal tumor and often occurs in the left colon with a poor prognosis. The progression of COAD is closely related to the tumor microenvironment, especially the hypoxia. Currently, few studies have reported the correlation between hypoxia-related genes and the prognosis of COAD patients. Furthermore, we constructed a prognostic model using four hypoxia-related genes to predict the prognosis of COAD patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To predict cancer, some scholars have used genes including SLC2A3 to construct models. A study constructed a hypoxia risk model using four hypoxia-related genes, TKTL1, SLC2A3, ALDOB, and ENO3, as a way to assess the tumor immune microenvironment and predict the overall survival of patients with colon adenocarcinoma (COAD), and thus develop hypoxia-targeted drugs for COAD patients (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To predict cancer, some scholars have used genes including SLC2A3 to construct models. A study constructed a hypoxia risk model using four hypoxia-related genes, TKTL1, SLC2A3, ALDOB, and ENO3, as a way to assess the tumor immune microenvironment and predict the overall survival of patients with colon adenocarcinoma (COAD), and thus develop hypoxia-targeted drugs for COAD patients (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org 13 Inhibition of CD36 might prove beneficial in repressing metastasis spread, which demonstrated clinical practice potential (Enciu et al, 2018). ENO3, as a glycolysis and hypoxia-related gene, could predict the prognosis and immune landscape of colon cancer patients (Cui et al, 2021;He et al, 2021;Mao et al, 2022). ENO3 could promote CRC cell proliferation and migration by promoting glycolysis metabolism (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in a hypoxic tumor microenvironment, the immune checkpoints, including PD1, PD-L1 and CTLA 4, are upregulated, as are the immunosuppressive cells. In such a state, effector T cells are inhibited and suppressive cells, such as regulatory T cells and tumor-associated macrophages, are in an increased amount [ 27 ]. In our samples, intratumoral immune cells were present in variable amounts.…”
Section: Discussionmentioning
confidence: 99%